A neuro-fuzzy linguistic approach to experimental parameters with silicon carbide grinding wheel (2010)
The paper presents a control system for grinding process using fuzzy rule-based model for estimating the grinding conditions at which wheel wears occur. The grinding parameters include circumferential speed of a grinding segment workpiece velocity and work depth of cut using silicon carbride grinding wheels. There was a wide range of applications over many types of mild steel materials and variious wheel wear values were records for predicting the grinding conditions. Grinding wheels with various wheel hardness grades ranging from soft (H grade) to hard (R grade) and wide range of grit sizes, ranging from coarse to fine.